A new genus of kangaroo (Marsupialia, Macropodidae) from the late Pleistocene of Papua New Guinea. Issue 2 (3rd July 2022) - Kerr, Isaac A. R.; Prideaux, Gavin J.
ABSTRACT: The extinct macropodine kangaroo, Protemnodon nombe, was first described in 1983 on the basis of two partial dentaries from a late Pleistocene deposit in Nombe Rockshelter, Papua New Guinea. As part of a review of Protemnodon, we noted that P. nombe differed from other members of the genus in several ways that pointed to a position outside of that genus and indeed all other known macropodine genera. The taxon possesses a unique combination of attributes of the dentary and lower dentition, including lower molars with a slight postmetacristid, a small postprotocristid and a gently S-shaped protolophid crest. The proportions of masticatory muscle insertion areas, including a broad masseteric canal for the deep masseter, resemble those of sthenurines, suggesting adaptation to tougher browsed vegetation than other New Guinean macropodines. A parsimony analysis suggests a divergence near the base of the Macropodinae, potentially in the early late Miocene. LSID of publication: urn:lsid:zoobank.org:pub:1458D336-3180-41FE-9DF5-DFAED7971807